Geosphere Profile of Tritis Cave in Gunung Kidul Yogyakarta as a Tourism Object - RB Suharta; Tristanti Tristanti; Yudan Hermawan (Postgraduate, University of Mataram, 2023)
The purpose of this study is to describe how the geosphere profile of Tritis cave. This study is very interesting to provide scientific input to the government in developing tourism in Gunung Kidul, Yogyakarta. The study method used is descriptive qualitative method and tends to use analysis. The theoretical basis is used as a basic reference in preparing the study report to match the conditions in the field. In addition, the theoretical basis can also provide an overview of the background of the study as material for discussion. The ability to collect data is an important factor in determining the validation of the study conducted. Data collection in this case is obtained secondarily, namely through documents or literature studies.The results of the study of geospheric phenomena that occur in the Maria Tritis cave are in the form of the main land formation is Karst with specific karst caves formed during the Pleiocene to Pleistocene. The dominant vegetation is teak trees. And the type of soil found around the maria tritis cave is a mediterranean soil type.